O-02 Study of the cortical control of the cardiac autonomic nervous system using intracerebral electrical stimulations. Issue 7 (July 2019) - Szurhaj, William; Edouard Alazard, Nicolas Reyns, Philippe Derambure, Renaud Lopes, Julien De jonckheere, Orane Demuynck,
Abstract : Background: The activity of the cardiac autonomic nervous system is modulated by cortical regions. The function of the insula in the cardiac autonomic control has been widely described in humans, but the roles of the other regions of the central autonomic network (such as the ventromedial prefrontal cortex, the amygdala or the anterior cingulate cortex) remain unclear. In order to better understand the role of the central autonomic network in the cardiac autonomic control, we studied the impact of intracerebral electrical stimulation of the insular cortex, the anterior cingulate cortex, the orbito-frontal cortex and the amygdala on the heart rate variability. Methods: We included 36 epileptic patients undergoing stereoencephalogram who were stimulated by trains (except for the amygala, which was stimulated by shocks). The vagal tone was quantified by computing the heart rate variability in high frequencies (HFV Index), before and after theelectrical stimulations. Results: A decrease in HFVI was observed after the stimulation of the postero-superior region of the insula bilaterally, but not in the inferior and antéro-superior parts of the insula, whereas an increase of HFVI was only observed after the stimulation of the left orbito-frontal cortex. Conclusions: Our results emphasize the role of the left orbito frontal cortex in the cardiac parasympathetic control. In the insula, the postero-superior part seems to be the main insular area involved in cardiac autonomic control.